The liquid phase oxidation of styrene with tungsten modified silica as a catalyst - Adam, Farook; Mohamed Iqbal, Mohammad Anwar (Elsevier BV, 2011)
Tungsten was incorporated into silica matrix using sodium silicate from rice husk at pH 10, 7 and 3. These catalysts were labeled as RHW-10, RHW-7 and RHW-3. The pH was found to have a strong influence on the structure of the resulting silica–tungsten species and its catalytic activity. Analysis suggests that the catalysts were composed of isolated [WO4]2− species, isolated tungsten species or low oligomeric tungsten oxide species and crystalline WO3 species. The catalytic activity was tested in the liquid phase oxidation of styrene using H2O2 as oxidant. RHW-3 showed better catalytic activity than RHW-10 and RHW-7 due to its higher tungsten loading. The reaction is proposed to be catalyzed by pertungstic acid like intermediate which was formed upon the interaction of tungsten oxo species (WO) with H2O2. Benzaldehyde was obtained via styrene oxide as the major product with 100% selectivity. RHW-3 could be re-used several times without losing its catalytic activity even though a small amount of tungsten species leached out from the support.